Assesment of empty fruit bunch compost and phosphorus availability: case study of different type of microorganisms / Nur Amira Ismail - Ismail, Nur Amira (Faculty of Plantation and Agrotechnology, 2017)
A case study is conducted to investigate the interaction of microorganisms with empty fruit bunch (EFB) compost in term of increasing phosphorus (P) availability. To address this, four treatments are set up which are control (T0), soil with EFB compost and Phosphate Solubilizing Bacteria (PSB) (T1), soil with EFB compost and Arbuscular mychorrhizae fungal (AMF) (T2) and soil with EFB compost with both PSB and AMF (T3). There are 5 replications involved in each treatment and this study is established within 7 weeks, using randomized complete block design (RCBD) trial. Soils (2kg for each sample) are mixed with EFB compost (400 g for each sample) before PSB and AMF being inoculated in the mixed soils. Analysis of sample is carried out every week. Besides, the paddy growth analysis is recorded to measure their growth rate in each sample respectively, considering weekly plant height and root biomass at the final week of experiments. Soil pH in soils is found to have significant increase by the highest mean value in T3 where the bacteria population also shows a rise in microbial analysis. The ultimate value of available P is in T0, followed by T3. Co-inoculation with PSB and AMF in T3 also resulted in the highest plant height, maximum amount of total P, Aluminium (Al) and Iron (Fe). In conclusion, the findings demonstrated that inoculation of PSB and AMF in soil amended with EFB compost can be seen as sustainable strategy for increasing P availability in soil and in enhancing growth rate of plants, but several considerations must be taken in ensuring the application of this technique can produce significant effects.